2018
DOI: 10.1021/acs.analchem.8b00298
|View full text |Cite
|
Sign up to set email alerts
|

Time-Gated Raman Spectroscopy for Quantitative Determination of Solid-State Forms of Fluorescent Pharmaceuticals

Abstract: Raman spectroscopy is widely used for quantitative pharmaceutical analysis, but a common obstacle to its use is sample fluorescence masking the Raman signal. Time-gating provides an instrument-based method for rejecting fluorescence through temporal resolution of the spectral signal and allows Raman spectra of fluorescent materials to be obtained. An additional practical advantage is that analysis is possible in ambient lighting. This study assesses the efficacy of time-gated Raman spectroscopy for the quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Although that this study showed that there is still a lot of work to do to harness the full potential of time-resolved CMOS SPAD line sensors for Raman spectroscopy, it should be noted that the CMOS SPAD-based Raman spectroscopy has already shown its potential in various conventionally challenging applications, such as Raman analyses through single optical fibers, analysis of fluorescent pharmaceuticals, quantification of pickle liquor and chemical imaging of human teeth and rare earth element bearing rocks [16], [29]- [32]. The field of CMOS SPAD-based Raman spectroscopy is still relatively young (the first conference paper about the topic was published less than a decade ago [11]) but the developments made in the sensor architectures and performances promise a bright future for the time-resolved CMOS SPAD-based Raman spectroscopy.…”
Section: Discussionmentioning
confidence: 90%
“…Although that this study showed that there is still a lot of work to do to harness the full potential of time-resolved CMOS SPAD line sensors for Raman spectroscopy, it should be noted that the CMOS SPAD-based Raman spectroscopy has already shown its potential in various conventionally challenging applications, such as Raman analyses through single optical fibers, analysis of fluorescent pharmaceuticals, quantification of pickle liquor and chemical imaging of human teeth and rare earth element bearing rocks [16], [29]- [32]. The field of CMOS SPAD-based Raman spectroscopy is still relatively young (the first conference paper about the topic was published less than a decade ago [11]) but the developments made in the sensor architectures and performances promise a bright future for the time-resolved CMOS SPAD-based Raman spectroscopy.…”
Section: Discussionmentioning
confidence: 90%
“…4d-i) has the further advantage that Raman spectra can be efficiently obtained in the presence of uorescence and other photoluminescent phenomena. 52,53 This is achieved through temporal rejection of the uorescence signal, which, unlike the near instantaneous Raman signal, typically occurs on the order of nanoseconds (or even longer). 54 This expands the range of possible glass materials (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…This type of Raman spectroscopy was designed for effective fluorescence suppression compared with the use of conventional Raman spectroscopy. [ 29 ]…”
Section: Methodsmentioning
confidence: 99%